The Development of user-centered advanced manufacturing technology new design practice or new marketing rhetoric? - Corbett, J. Martin (International journal of human factors in manufacturing)
This article examines the values and assumptions held by producers of CNC machien tools in the U. K., Germany, and Japan. Survey findings are presented which reveal that, despite serving different customers/users, producers share similar (essentially technocentric) views on what constitutes optimal CNC design. Implications for the development of user-centered advanced manufacturing systems are discussed in the light of these findings.